The Land Suitability for Settlement in the Coastal Area of Bolaang Mongondow Utara Regency - Lamunte, Laras; Maryati, Sri; Yusuf, Daud (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2025)
This study aims to evaluate the land suitability for residential development in the coastal areas of Bolaang Mongondow Utara Regency. A spatial analysis approach based on Geographic Information Systems (GIS) was employed, utilizing techniques such as buffering, overlay, and scoring to assess the suitability parameters. The evaluated parameters include slope, soil type, accessibility (Distance to Main Road), land use, distance to coastline, and distance to river. The spatial analysis results indicate that the majority of the study area is categorized as marginally suitable for settlement (18,619.35 ha or 55.73%), while highly suitable areas account for 1,847.10 ha (36.05%). These findings provide important insights for regional planning by the local government in managing coastal residential development.